Therapeutic applications of nanobots and nanocarriers in cancer treatment - Zaitoon Khan (22504295) (2025)
Cancer remains a pressing global health concern, burdening individuals, families, and healthcare systems worldwide, mainly because of the limited availability of therapeutic options. These days, nanotechnology is revolutionizing cancer research by offering promising drug delivery systems. Among these, nanobots and nanocarriers are key nanotechnology components, offering groundbreaking strategies in cancer therapy by delivering drugs, enhancing diagnostics, and preventing diseases at molecular levels. Nanobots and nanocarriers, engineered at sizes ranging from 1 to 100 nm, demonstrate biocompatibility with cellular systems, offer precise drug delivery, and reduce side effects compared to conventional therapies such as chemotherapy and surgery. Research efforts now focus on transitioning nanobots and nanocarriers from laboratories to clinics, aiming for precision medicine, targeted drug delivery, enhanced therapy efficacy, and minimal side effects. This review aims to highlight the potential of nanobots and nanocarriers in cancer treatment and provide insights into their role in paving the way for clinical applications and improving outcomes in cancer therapy. Other Information Published in: Analytical Sciences License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s44211-025-00799-5